Stephen Biesty's incredible body cross-sections - Platt, Richard (DK Publishing, 2020)
Presents full color, double-page spread cross-section illustrations of the human body, from the eye and the brain to the skeleton and the reproductive system. Offers short descriptions of each detailed body part or system.